Історична пам’ять як чинник формування ідентичності - Готра, Олена Броніславівна (Житомирський державний університет ім. Івана Франка, 2015)
У статті проаналізовано феномен історичної пам‘яті як чинник формування національної ідентичності. Розглянуто теоретичне обґрунтування та важливі функції історичної пам‘яті для зміцнення національної самосвідомості і формування державної політики пам‘яті. Досліджено значення і роль історичної пам‘яті в системі суспільних цінностей, її вплив на критичне сприйняття власного минулого та формування національних символів. Автор дійшов висновку, що історична пам‘ять та історична свідомість формують історичну культуру, яка, з одного боку, виступає потужним засобом національної самоідентифікації, а з іншого – сприяє порозумінню між представниками різних національних проектів.

The article analyzes the phenomenon of historical memory as a factor in the formation of national identity. Theoretical justification of the important functions of historical memory to strengthen national identity and the formation of public policy memory. Investigated the role of historical memory in the system of social values, its impact on the critical perception of their own past and the formation of national character. Today's research of values and motivations can change society, become its own historical experience, mentality, to rich spiritual and moral traditions of multinational Ukrainian people. The article investigate the historical memory, it can give a chance to people to understand their role in history, to predict the future, to feel themself as a descendant of the great Ukrainian people and feel confident in a globalized world. The author notes that based on past patterns of historical memory should provide answers to the problems of the present and forecast of its development future generation. The article proves that national identity can play through rethinking history and new approaches. The main thing is to take into account the lessons of history, reinterpret historical events and analyze them in view of the future. Deep analytical analysis of past dialogue requires its different interpretations, which will be the basis of a new paradigm of the modern historical thinking in order to create and develop democratic and tolerant society. The main thing is the ability to hear the other hand, value their own and others' memories, searching in the experience of the past responses to project the future and open dialogue. The author came to the conclusion that the historical memory and historical consciousness historical form a culture that, on the one hand, acts as a powerful tool of national identity, on the other hand, contributes to mutual understanding between representatives of different national projects.
Keywords: історична пам‘ять; національна ідентичність; історична свідомість; суспільні цінності; культура; historical memory; national identity; historical consciousness; social values; culture